La ciudad perdida - Hervé, Francisco, 1971-; Vadell, Jaime (Panchito Films : La Fábrica Nocturna Productions, 2016)
Aysén, a region in Chilean Patagonia, is the size of England but has only 90,000 inhabitants. They live isolated with nearly no roads in a stunning rough landscape. Somewhere in this lost world, a mysterious city is hiding. Five hundred years ago a group of conquerors built a city entirely of gold. As legend describes, whoever sets foot on it becomes immortal but loses their memory. It is the City of the Lost Caesars.